Infinite dilution activity coefficients and gas-to-liquid partition coefficients of organic solutes dissolved in 1-sec-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and in 1-tert-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide. (4th July 2019) - Mutelet, Fabrice; Baker, Gary A.; Ravula, Sudhir; Qian, Ellen; Wang, Lainey; Acree, William E.
ABSTRACT: Inverse gas chromatography was used to measure infinite dilution activity coefficients and gas-to-liquid partition coefficients for 48 organic solute probes in either 1- sec -butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide or 1- tert -butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide in the temperature range from 323.15 to 373.15 K. Partial molar excess enthalpies of solution were calculated from the variation of the infinite dilution activity coefficients with temperature. Abraham model correlations were also derived from the experimental partition coefficient data. The derived Abraham model correlations describe the observed partition coefficients to within 0.11 log units.